The Silent Europe (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2020)
The contribution deals with a number of areas in ancient Europe where the epichoric languages are predominantly and primarily onomastic. After a brief consideration of certain theoretical problems, it starts off with a survey of the “Ligurian” set of questions and then moves to the vast region which has been formally considered a domain of the “Illyrian” language. The paper discusses the available data and reviews anthroponymic provinces traditionally selected in this area as well as geographical names, also going beyond the traditional borders of the “Illyrian” space.